Short‐term oncological and surgical outcomes of robot‐assisted radical prostatectomy: A retrospective multicenter cohort study in Japan (the MSUG94 group). Issue 4 (4th May 2022) - Kato, Daiki; Ebara, Shin; Tatenuma, Tomoyuki; Sasaki, Takeshi; Ikehata, Yoshinori; Nakayama, Akinori; Toide, Masahiro; Yoneda, Tatsuaki; Sakaguchi, Kazushige; Teishima, Jun; Makiyama, Kazuhide; Inoue, Takahiro; et al.
Abstract: Introduction: We evaluated oncological outcomes of patients undergoing robot‐assisted radical prostatectomy (RARP) for prostate cancer (PCa) and their perioperative complications in Japan. We investigated clinical and pathological covariates to predict biochemical recurrence (BCR) after RARP. Methods: A retrospective multicenter cohort study was conducted in RARP patients with PCa at 10 institutions in Japan. Pre‐ and postoperative covariates were collected from enrolled patients. The primary endpoint was defined as biochemical recurrence‐free survival (BRFS). Additionally, the association between BCR and clinicopathological covariates was determined. Results: We enrolled 2670 patients in this study. The median follow‐up period was 26.0 months. RARP‐related perioperative complications were identified in 198 patients (7.4%), including 69 patients (2.6%) with grade 3/4 complications according to the Clavien–Dindo classification. The 2‐year BRFS was 88.0%. Using the Kaplan–Meier method, initial prostate‐specific antigen (PSA) level of ≤7.6 ng/mL, biopsy and pathological Gleason score (GS) of ≤7, clinical and pathological T1/2, and low/intermediate risks according to the National Comprehensive Cancer Network risk classification, and negative surgical margin status had significant BRFS than their counterparts. In multivariate analysis, initial PSA, biopsy and pathological GS, clinical and pathological T stage, and surgical margin status significantly correlated with BCR after RARP. Conclusion: In this study, RARP achieved a lower incidence of perioperative complications than other studies.